Data Collection and Recharging of Sensor Node by Mobile Sink in Wireless Sensor Network - Zafor, Hanif; Sheikh, Tasher Ali; Mazumdar, Nabajyoti; Nag, Amitava (International Journal of Sensors Wireless Communications and Control, 2025)
The wireless sensor network (WSN) has limited battery and storage capacity. The main challenge in static sink nodes is the lack of energy and data transfer to the base station (BS). A mobile sink (MS) is an excellent way to handle these difficulties in WSN. The use of an MS solution not only ensures long-term network functionality, but also improves network performance. In this paper, the MS-based data collection and recharging, mobile device is used for data collection from sensor nodes and recharging the sensor nodes throughout the network whenever required. There are two types of MS-based solutions described as (i) Mobile devices for data collection from sensor nodes in the network. (ii) Mobile device for collecting data and recharging sensor nodes from the network. Finally, in this paper, we presented the advantages, disadvantages, and other criteria of both types. Also, a potential framework is presented for data collection and recharging of sensor nodes by MS in WSN. The core contribution of this paper is present the state of art and future roadmap for data collection and recharging of sensor nodes by MS in WSN. The identification of the main open challenges and future direction in this research area are also highlighted and discussed.
Keywords: Wireless sensor network (WSN)